Decreased Plasma Oxytocin Levels in Patients With PTSD - Carmassi, Claudia; Marazziti, Donatella; Mucci, Federico; Della Vecchia, Alessandra; Barberi, Filippo Maria; Baroni, Stefano; Giannaccini, Gino; Palego, Lionella; Massimetti, Gabriele; Dell’Osso, Liliana (Frontiers in Psychology, 2021)
Introduction. Although the pathophysiology of post-traumatic stress disorder (PTSD) is still unclear, growing preclinical evidences suggest that oxytocin, a pleiotropic hormone, is possibly involved. However, direct studies on oxytocin in PTSD patients are a few. Therefore, the aim of the present study was at exploring plasma oxytocin levels in PTSD patients, as compared with healthy subjects. Materials and methods Twenty-six outpatients (12 men, 13 women) suffering from PTSD, and 26 healthy subjects (13 men, 12 women, were included. The patients were assessed through the structured clinical interview for DSM-IV-, research version, patient edition (SCID-I/P), and the Impact for Event Scale revised (IES-R). All subjects underwent three venous blood samples for the subsequent oxytocin radioimmuno assay. Results. 15. The OT levels (mean ± SD, pg/ml) were significantly lower in the patients than in the control subjects (4.37±1.61 vs 5.55± 2.18, p > 0.001) (table 2). No correlations were detected between IES total score, subscales or single items and OT plasma levels. Again, no difference between men and women was detected in the patients’ group, while healthy control women showed higher OT levels than men. Discussions. The findings of the present study, while indicating the presence of decreased plasma OT levels in PTSD outpatients of both sexes, as compared with healthy control subjects, would support the possible involvement of oxytocin the pathophysiology of PTSD. However, given the complexity of the clinical picture, future studies are necessary to understand the role and level of oxytocin in PTSD.